Cytokine profiles in interstitial fluid from chronic atopic dermatitis skin. (18th May 2015) - Szegedi, K.; Lutter, R.; Res, P.C.; Bos, J.D.; Luiten, R.M.; Kezic, S.; Middelkamp‐Hup, M.A.
Abstract Background The in vivo levels of inflammatory mediators in chronic atopic dermatitis (AD) skin are not well‐defined due to the lack of a non‐invasive or minimally invasive sampling technique. Objectives To investigate the cytokine milieu in interstitial fluid (ISF) collected from chronic lesional AD skin as compared to ISF from non‐lesional AD skin and/or healthy donor skin. Methods ISF was obtained using a minimally invasive technique of creating micropores in the skin by a laser, and harvesting ISF through aspiration. We determined the levels of 33 cytokines by Luminex and ELISA in ISF and plasma from sixteen AD patients and twelve healthy individuals. In seven AD patients, we analysed the IL‐13, IL‐31, IL‐17, IL‐22 and IFN‐γ production by T cells isolated from lesional skin. AD patients were genotyped for the filaggrin gene (FLG)‐null mutations 2282del4, R501X, R2447X and S3247X. Results Twenty‐five of 33 examined mediators were detected in the ISF. The levels of IL‐1α, IL‐1β, IL‐18, IL‐1RA, IL‐5, IL‐13, IL‐6, IL‐8, TNF‐α, RANTES(CCL‐5), MIG(CXCL‐9), IP‐10(CXCL‐10), TARC(CCL‐17), VEGF and G‐CSF showed significant differences between either lesional, non‐lesional and/or healthy skin. IP‐10 levels in ISF from lesional and non‐lesional AD skin showed significant correlation with IP‐10 blood levels. IP‐10 also showed a significant correlation with clinical severity (SCORAD), as did IL‐13. Levels of both IP‐10 and IL‐13 were more pronounced in patients with FLG‐null mutations. Furthermore, FLG‐null mutation carriers had more severe AD. Conclusion The presented minimally invasive technique is a valuable tool to determine the in vivo cytokine profile of AD skin.